Crampology: measurement and treatment of muscle cramps - Katzberg, Hans (Henry Stewart Talks, 2023)
Assessing muscle cramp severity, Toronto Clinical Cramp Index, Patient-centered cramp care, non-pharmacological cramp treatments, Pharmacological cramp treatments, magnesium supplementation, Quinine and its derivatives, Mexiletine, Botulinum toxin